Refusing ‘bare life‘ – Belo Monte, the riverine population and their struggle for epistemic justice - Weißermel, Sören; Chaves, Kena Azevedo (DIE ERDE – Journal of the Geographical Society of Berlin, 2020)
The installation of the hydroelectric power plant Belo Monte in the Brazilian Amazon displaced more than 40,000 people, among them numerous riverine families who were not recognized as such. Their displacement resulted in the loss of their territory and the forced abandonment of their way of life. Struggling against their precarization and for recognition, affected riverine people founded a Riverine Council as a political body through which they organized themselves and reclaimed interpretative power over their ‘being riverine’. Discovering the category of traditional people as a legal shell to introduce their epistemic and ontological perspectives, they tried to force the state and the construction consortium to recognize their rights, guarantee access to their territories and, hence, compensate for environmental injustices. This paper focuses on the epistemic dimension both within the installation of Belo Monte and within the resistance struggle of the riverine population. For this purpose, we use a decolonial framing of Agamben’s (2002; 2005) perspective on the state of exception and the assignment of bare life that considers the epistemic character of the coloniality of power working within (see Mignolo 2005; Quijano 2009). This forms the basis for the occurrence of epistemic injustices (see Fricker 2007), which is discussed in connection with the environmental justice debate. In order to shed more light on the mechanisms of the production of disposable and bare life and the possibilities of resistance within the struggle for epistemic justice, we finally add the idea of precarization and performative resistance (see Butler 2009; Butler and Athanasiou 2013).